2019
DOI: 10.1002/jcb.28378
|View full text |Cite
|
Sign up to set email alerts
|

Leptin rs2167270 G > A (G19A) polymorphism may decrease the risk of cancer: A case‐control study and meta‐analysis involving 19 989 subjects

Abstract: Accumulating evidence has suggested that leptin (LEP) is very important for the development of cancer. Recently, a number of case-control studies about the relationship of the rs2167270 G > A (G19A) variants in the LEP gene with the risk of cancer have yielded inconsistent results. In this study, we have carried out a casecontrol study [1063 esophagogastric junction adenocarcinoma (EGJA) cases and 1677 controls] in a Chinese population. Furthermore, we carried out a pooledanalysis of 13 studies involving 8059 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 31 publications
(94 reference statements)
0
17
1
Order By: Relevance
“…The LEP gene is polymorphic. And LEP SNPs may influence the risk of cancer 16. The rs7799039 G>A (G2548A) polymorphism in the LEP gene is the most widely studied for its relationship between this locus and the risk of human diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The LEP gene is polymorphic. And LEP SNPs may influence the risk of cancer 16. The rs7799039 G>A (G2548A) polymorphism in the LEP gene is the most widely studied for its relationship between this locus and the risk of human diseases.…”
Section: Introductionmentioning
confidence: 99%
“…37 However, another Chinese study indicated that LEP G19A polymorphism contributed to less risk for esophagogastric junction adenocarcinoma. 38 As for prostate cancer, two studies obtained it was not heavily associated with LEP G19A polymorphism. 39,40 Next, several studies addressing the relationship between non-Hodgkin's lymphoma (NHL) risk and this polymorphism yielded conflicting findings.…”
Section: Discussionmentioning
confidence: 98%
“…This polymorphism was correlated to cancer risk. [33][34][35][36][37][38][39][40][41][42][43][44][45] However, the existing findings in different types of cancers are discrepant. Furthermore, no researchers have studied the relationship between G19A polymorphism and the risk of GC.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship was evaluated by using STATA software (version 12.0). We used an online calculator ( http://ihg.gsf.de/cgi-bin/hw/hwa1.pl ) to determine whether the genotype distribution of mir-499 rs3746444 agreed with Hardy–Weinberg equilibrium (HWE) [ 25 ]. Since the heterogeneity could influence the assessment of association, we used Q -statistical test and I 2 test to study the heterogeneity.…”
Section: Methodsmentioning
confidence: 99%